Loss of GRHL3 leads to TARC/CCL17-mediated keratinocyte proliferation in the epidermis. Issue 11 (November 2018) - Goldie, Stephen; Cottle, Denny; Tan, Fiona; Roslan, Suraya; Srivastava, Seema; Brady, Rhys; Partridge, Darren; Auden, Alana; Smyth, Ian; Jane, Stephen; Dworkin, Sebastian; Darido, Charbel
Abstract Identifying soluble factors that influence epidermal integrity is critical for the development of preventative and therapeutic strategies for disorders such as ichthyosis, psoriasis, dermatitis and epidermal cancers. The transcription factor Grainyhead-like 3 (GRHL3) is essential for maintaining barrier integrity and preventing development of cutaneous squamous cell carcinoma (SCC); however, how loss of this factor, which in the skin is expressed exclusively within suprabasal epidermal layers triggers proliferation of basal keratinocytes, had thus far remained elusive. Our present study identifies thymus and activation-regulated chemokine (TARC) as a novel soluble chemokine mediator of keratinocyte proliferation following loss ofGRHL3 . Knockdown ofGRHL3 in human keratinocytes showed that of 42 cytokines examined, TARC was the only significantly upregulated chemokine. Mouse skin lackingGrhl3 presented an inflammatory response with hallmarks of TARC activation, including heightened induction of blood clotting, increased infiltration of mast cells and pro-inflammatory T cells, increased expression of the pro-proliferative/pro-inflammatory markers CD3 and pSTAT3, and significantly elevated basal keratinocyte proliferation. Treatment of skin cultures lackingGrhl3 with the broad spectrum anti-inflammatory 5-aminosalicylic acid (5ASA ) partially restored epidermal differentiation, indicating that abnormal keratinocyte proliferation/differentiation balance is a key driver of barrier dysfunction following loss ofGrhl3, and providing a promising therapeutic avenue in the treatment ofGRHL3 -mediated epidermal disorders.